Effect of pre and post emergence herbicides on microbial biomass carbon and dehydrogenase activity in soils - Amritha, K.; Devi, K.M. Durga (Journal of Tropical Agriculture, 2017)
A pot culture experiment in rice was conducted to study the effect of pre and post emergence herbicides on microbial biomass carbon and dehydrogenase activity in soils. Results indicated that the herbicides had negative effect on microbial biomass carbon. Dehydrogenase activity also showed a decline due to the application of herbicides, but to a lesser magnitude than microbial biomass carbon. The adverse effect was pronounced only at 15 days after application of herbicides and followed the order viz., pendimethalin > bispyribac-sodium > oxyfluorfen > cyhalofop-butyl. The adverse effects were of lower magnitude in the soils of high organic matter content.